Social-Ecological Factors Associated With Higher Levels of Resilience in Children and Youth After Disaster: The Importance of Caregiver and Peer Support - McDonald-Harker, Caroline; Drolet, Julie L.; Sehgal, Anika; Brown, Matthew R. G.; Silverstone, Peter H.; Brett-MacLean, Pamela; Agyapong, Vincent I. O. (Frontiers in Public Health, 2021)
Children and youth are among the most vulnerable to the devastating effects of disaster due to the physical, cognitive, and social factors related to their developmental life stage. Yet children and youth also have the capacity to be resilient and act as powerful catalysts for change in their own lives and wider communities following disaster. Specific factors that contribute to resilience in children and youth, however, remain relatively unexplored. This article examines factors associated with high levels of resilience in 100 children and youth aged 5 to 18 years old who experienced the 2016 Fort McMurray, Alberta wildfire. A mixed-methods design was employed combining quantitative and qualitative data. Quantitative data was obtained from the Children and Youth Resilience Measure (CYRM-28) which measured individual, caregiver, and context factors influencing resilience processes among the participants. Qualitative data was collected through semi-structured interviews to gain further insight into the disaster experiences of children and youth. Quantitative findings reveal higher than average levels of resilience among the participants compared to normative scores. Qualitative findings suggest high levels of resilience were associated with both caregiver factors (specifically physical caregiving), and individual factors (primarily peer support). We discuss how physical caregiving and peer support during and after the wildfire helped mitigate the negative effects of disaster, thus bolstering children and youth’s resilience. Implications for understanding the specific socio-ecological factors that facilitate and support resiliency processes and overall recovery of children and youth following disaster are also discussed.